Marāṭhī kavi viruddha Pro. Vāsudeva Baḷavanta Paṭavardhana - Tivārī, Du. Ā. (Durgāprasāda Āsārāma), 1887-1939 (SAMP early 20th-century Indian books project, 1929)
Refutation of Kāvya āṇi kāvyodaya, critical work on Marathi poets, by Vāsudeva Baḷavanta Paṭavardhana, 1870-1921.